Pengaruh Penerapan SAP, Sistem Akuntansi Keuangan Daerah, Kompetensi SDM, dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan - Yuliana Yuliana; Muhamad Rifandi (Financial and Accounting Indonesian Research, 2025)
Financial reporting in the government system is crucial to improve its quality. Several factors influence the quality of financial reports. This study aims to examine the effect of the implementation of Government Accounting Standards (SAP), the Regional Financial Accounting System (SAKD), human resource competency (HR), and the use of information technology on the quality of financial reports of the Banggai Laut Regency Government. The research method used is a quantitative approach by distributing questionnaires to 81 respondents from 27 SKPD, and the data analyzed using multiple linear regression. The results show that the implementation of SAP, human resource competency, and the use of information technology have a positive and significant effect on the quality of financial reports. In contrast, the regional financial accounting system (SAKD) does not have a significant effect on the quality of financial reports. These findings contribute to expanding the study of public sector accounting by enriching the four variables tested in an integrated manner. These findings provide practical impacts for the Banggai Laut Regency government regarding the importance of implementing accounting standards and information technology in realizing reliable and accountable financial reports. This study still has limitations, namely in the geographical scope of Banggai Laut Regency, so the results of the study cannot be generalized to other regions. The research was also limited to quantitative methods, thus limiting our understanding of the phenomena. Future researchers can implement a mixed methods approach and expand the study to include government agencies in other regions to gain a more comprehensive understanding.